A Critical Review into the Socioeconomic Issues Surrounding the Human Papillomavirus Vaccine - Rowlands, Laura (2010)
ABSTRACT A critical review of the literature was sought to answer the research question: “What is the current position of evidence behind the recommendations for the HPV vaccination programme and the consequent socioeconomic implications?”